AVALIAÇÃO INSTITUCIONAL E DESEMPENHO DOCENTE EM UNIVERSIDADES PÚBLICAS FEDERAIS: ANÁLISE DE DADOS TEXTUAIS DE UMA FACULDADE DE ENGENHARIAS - Vanessa Cristina Marracini (2024)
This study focuses on the institutional self-assessment process of a public higher education institution, whose objective is to analyze the comments written by undergraduate students of a college of engineering about teaching performance in the open space of the internal institutional assessment questionnaire for the years 2022 and 2023. The methodology applied was divided into two axes: the first was based on carrying out bibliographic and documentary research, in addition to the use of the systematic literature review technique using the virtual environment Parsif.al to define the bibliographic portfolio on institutional assessment and teaching performance, together with the general regulations and current legislation specific to the subject. The second axis was developed through the collection and content analysis of data extracted from the institutional assessment reports for the years 2022 and 2023 using the IRAMUTEQ software, which generated vast statistical and graphic material essential for understanding and interpreting the data worked on. The analysis of the results revealed gaps in the evaluation process, which provided an opportunity to develop a proposal for improvements to the existing process, in order to direct efforts towards more efficient management aimed at improving the quality of education, which resulted in the presentation of a technical and technological product presented to the competent institutional bodies as a result of the efforts undertaken to complete the Professional Master's Degree in Public Administration. In this sense, this research translates pertinent information for future studies aimed at understanding institutional self-evaluation and teaching performance, as well as the entire process that involves them.